ANALYSIS OF THE EXPORT COMPETITIVENESS OF FRUITS UNDER HS CODE 080450 (GUAVA, MANGO, AND MANGOSTEEN) FROM INDONESIA IN THE INTERNATIONAL MARKET - Hanifah Ningrum; Djeimy Kusnaman; Sawitania Situmorang (Universitas Sebelas Maret, 2026)
Tropical fruits such as mango, mangosteen, and guava are amongIndonesia’s leading horticultural products. Mangosteen fruit is the largest export toIndonesia’s total fruit exports. However, Indonesia's mangosteen export share is stillvery low, and this should be maximized. Mango also has promising exportopportunities as it occupied the 21st position as an exporting country in 2021. Guava also has same condition with an increase in export and already having marketsabroad, such as Singapore and Korea. This study aims to analyze the competitivenessof Indonesian mangosteen exports in the international market and compare with othermangosteen-exporting countries in the international market to determine the factorsthat affect mangosteen competitiveness. The data used are secondary data from 2003to 2022. The analysis methods used were RCA, ECI, TSI and multiple regressionanalysis were used. The RCA analysis results show that Indonesian mangosteen hasa comparative advantage with a value of 1.053. The results of the ECI analysis showthat Indonesian mangosteen has a competitive advantage and experiences anincreasing export trend with a value of 1.217 and TSI shows that Indonesia tends tobe a mangosteen exporting country and is at the maturity stage with a value of 0.903.However, Indonesia's competitive position is still below that of other countries suchas Thailand, India, Peru and Kenya. Factors that significantly affect Indonesia’s RCAare Indonesia’s and Thailand’s export volume and Indonesia’s export prices.